2021
DOI: 10.1002/jctb.6787
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of d‐lactic acid productivity by introducing Escherichia coli acetyl‐CoA synthesis pathway in engineered Saccharomyces cerevisiae

Abstract: BACKGROUND d‐Lactic acid (d‐LA) is gaining increased attention as it can be applied in the food, pharmaceutical, cosmetic, polylactic acid and textile industries. Acid‐tolerant Saccharomyces cerevisiae is often engineered to produce organic acids. For the pyruvate decarboxylases (PDCs) or alcohol dehydrogenase 1 (ADH1) disrupted strains, the productivity of d‐LA significantly decreases due to the accumulation of acetaldehyde and acetic acid. To overcome the problem, Escherichia coli acetylating acetaldehyde de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…47 Knocking out pyruvate decarboxylase Pdc1 and acetaldehyde dehydrogenase Ald6 was also an effective strategy to increase the pyruvate pool by weakening the synthesis of acetate. 48 However, the titer of D-pantothenic acid in strain DPA142, DPA143, or DPA151 did not increase substantially. It was similar to the situation of knocking out Lpd1 (DPA146) leading to a branch to tricarboxylic acid cycle.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…47 Knocking out pyruvate decarboxylase Pdc1 and acetaldehyde dehydrogenase Ald6 was also an effective strategy to increase the pyruvate pool by weakening the synthesis of acetate. 48 However, the titer of D-pantothenic acid in strain DPA142, DPA143, or DPA151 did not increase substantially. It was similar to the situation of knocking out Lpd1 (DPA146) leading to a branch to tricarboxylic acid cycle.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…This may be attributed to the fact that the elimination of the glycerol pathway improves not only the pyruvate flux but also the serine flux and increases the catalytic efficiency of KPHMT . Knocking out pyruvate decarboxylase Pdc1 and acetaldehyde dehydrogenase Ald6 was also an effective strategy to increase the pyruvate pool by weakening the synthesis of acetate . However, the titer of d -pantothenic acid in strain DPA142, DPA143, or DPA151 did not increase substantially.…”
Section: Resultsmentioning
confidence: 99%
“…The gene ADH1 encodes alcohol dehydrogenase, which is the primary enzyme for the reoxidation of NADH in yeast. Zhong et al (2021) showed that inactivation of ADH1 caused the accumulation of NADH, resulting in the imbalance of NADH/NAD and growth retardation [52]. The upregulation of ACH1 and ADH1 in S. spartinae W9 cells cultured with 0.1% β-glucan led to higher colonization ability in strawberry wounds and improved biocontrol efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…20 The genes encoding PDH complex, ACS, PANK and other acetyl-CoA forming enzymes were introduced into microorganisms to generate diverse cell factories overproducing acetyl-CoA. 18,21–23 These cell factories were generally used as a chassis for producing acetyl-CoA-derived chemicals. 21–24 The biosynthesis of P6′′A using self-producing acetyl-CoA, however, in cell factories has never been documented.…”
Section: Introductionmentioning
confidence: 99%
“…18,21–23 These cell factories were generally used as a chassis for producing acetyl-CoA-derived chemicals. 21–24 The biosynthesis of P6′′A using self-producing acetyl-CoA, however, in cell factories has never been documented.…”
Section: Introductionmentioning
confidence: 99%